Sintering atmosphere effect on Al-0.2Mg alloy - Muhammad Firdaus Rosli (Universiti Malaysia Perlis, 2008)
The effect of sintering atmosphere on mechanical properties and microstructure of Al-0.2Mg alloy were investigated. In this study, one type of parameter were used that was; different sintering atmosphere. Al and Mg were then mixed in milling jar for 3hours by 300rpm. The mixture then was sintered at 610oc for 6 hours of soaking time at 5°C/min for heating rate. The characterization of the sample such as the porosity, density, shrinkage, hardness and weight loss were carried out in order to determine the properties of the final product. The sample were also been analyzed using Image analyzer to capture microstructure of the sample. From the experiments, there were large effects of sintering atmosphere on the properties of materials. Materials that were sintered in common atmosphere shows better properties compared to samples that were sintered in argon and nitrogen gases atmosphere.